PERSEPSI PETANI KELAPA SAWIT POLA SWADAYA DALAM PENERAPAN INDONESIA SUSTAINABILTY PALM OIL ( ISPO DI KABUPATEN KAMPAR) - Rosnita Rosnita; Yulia Andriani; Roza Yulida; Syaiful Hadi; Fanny Septya (Jurnal Ilmu Lingkungan, 2022)
Farmers of palm oil requaired 1. Farmers of palm oil are mandatorily required to follow the ISPO standar in their business. 2. The problem arise due to mobilty to implement the standard. 3. The purpose of this study was examine the perception of palm oil farmers to the concept of ISPO. 4. The study was conducted from March 2019 to September 2020 using survey methods. Stratified Random Sampling with a sample number of 90 people from 3 sub-districts (Tapung Hulu, Tapung Hilir and Tapung). Were done  the analysis was performed  descriptively. The results showed  that the characteristics of palm oil were full filled still not  still not the principles of ISPO, especially in the principle of sustainable business improvement and the principle of environmental management and monitoring. Farmers have a perception that they are still less able to apply the four principles of ISPO, especially in improving sustainable business and environmental management and monitoring.